State of kidney function and features of metabolic status changes in patients with hypertensive disease with different forms of extrasystols - Kuzminova, Natalia; Ivankova, A.; Lozinsky, S.; Knyazkova, Iryna; Kulchytska, O.; Gavrylyuk, A. (My University, 2019)
56 patients (65 men and 91 women) of middle age with stage II essential hypertension (EH II) were examined. The main group consisted of 124 of them with the evidence of frequent supraventricular (SVPB) (74 persons) or ventricular premature beats (VPB) (50 persons) established by daily ECG monitoring. The comparison group included 32 patients with EH II stage without arrhythmia. Patients in the main group were significantly more likely to have a hypertensive history, they had significantly more burdened cardiovascular heredity, a significant increase in body mass index and incidence of abdominal obesity, fasting glucose and uric acid (p <0.05). The patients with frequent VPB compared with patients with SVPB had more marked differences in most of the analyzed parameters on the background of significant (p <0.05) reduction of the glomerular filtration rate. Therefore, these changes in metabolic status may contribute to the occurrence of VPB in patients with hypertension.
Keywords: essential hypertension; supraventricular premature beats; ventricular premature beats; glomerular filtration rate